Paramagnetic resonance studies of phase transitions in condensed materials - Owens, F. J. (Phase transitions, 1985)
The use of electron paramagnetic resonance (EPR) as a tool to study various kinds of phase transitions in condensed materials is discussed. The subject is reviewed by considering representative examples of studies in the different kinds of phase transitions. Structural phase transitions in solids, dynamics of formation of Slater configurations in KDP type ferroelectrics, temperature dependence of ordering in liquid crystals, studies of the dynamics of chain motion in glass to rubber transitions in polymer systems as well as magnetic transitions are discussed.